2019
DOI: 10.1002/jgh3.12137
|View full text |Cite
|
Sign up to set email alerts
|

Association between local alcoholic beverages and amoebic liver abscess in the Indian subcontinent: Weird but true!

Abstract: Many studies from the Indian subcontinent have revealed a strong association between amoebic liver abscess and consumption of toddy – an alcoholic beverage containing fermented palm juice. This article discusses the issues related to this potentially important problem so that appropriate preventive steps can be taken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Previous studies from some parts of India[ 19 ] and Sri Lanka[ 20 21 ] have shown that consumption of locally made alcohol such as toddy, which is usually prepared in unhygienic conditions, is a significant risk factor for the development of ALA. No such association was found by Jha et al . [ 4 ] Alcohol consumption also causes hepatic damage, and alcoholics often have poor nutritional status leading to relative immunodeficiency state, thereby increasing the chances of ALA.[ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from some parts of India[ 19 ] and Sri Lanka[ 20 21 ] have shown that consumption of locally made alcohol such as toddy, which is usually prepared in unhygienic conditions, is a significant risk factor for the development of ALA. No such association was found by Jha et al . [ 4 ] Alcohol consumption also causes hepatic damage, and alcoholics often have poor nutritional status leading to relative immunodeficiency state, thereby increasing the chances of ALA.[ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the highest consumption occurred during the dry season, which correlated to peak alcohol sales in the northern region [7,10]. Currently, data supports an association between the consumption of indigenous alcoholic beverages and ALA [64,68]. While it is unclear how E. histolytica enters the alcoholic beverages prior to consumption to cause disease, theories suggest that it may be due to factors such as water contamination, unhygienic practices in toddy taverns such as open-air defecation, improper hand hygiene, and water filtration practices (cysts are resistant to low doses of chlorination) [9,69].…”
Section: Alcohol Consumptionmentioning
confidence: 99%
“…Numerous mechanisms have been postulated to explain the link between alcohol consumption and the development of ALA. One such explanation is the 'iron hypothesis', whereby iron sequestration in the liver leads to overload, preventing alcohol metabolism via aldehyde dehydrogenase, requiring iron as a co-factor [68]. Others have suggested the role of alcohol-induced hepatocyte injury to result in reduced immunity, and thus increased susceptibility to infection due to damage of Kupffer cells [64].…”
Section: Alcohol Consumptionmentioning
confidence: 99%
“…Strong association with alcohol consumption: Alcohol consumption increases the risk of developing ALA. A history of significant alcohol consumption is present in up to 85% of patients with ALA[ 1 , 26 , 27 ]. A number of studies from the Indian subcontinent have found a strong correlation between the incidence of ALA and the intake of local alcoholic beverages such as toddy[ 1 , 20 , 26 - 28 ].…”
Section: Clinico-epidemiological Characteristicsmentioning
confidence: 99%
“…A number of studies from the Indian subcontinent have found a strong correlation between the incidence of ALA and the intake of local alcoholic beverages such as toddy[ 1 , 20 , 26 - 28 ]. Moreover, alcoholics have been found to have larger ALA, more complications, and a longer recovery period[ 27 ]. The precise mechanism of how alcohol confers the susceptibility to ALA is yet to be defined.…”
Section: Clinico-epidemiological Characteristicsmentioning
confidence: 99%